Students’ Problems in Mastering Arabic Vocabulary at MTs An-Noor Paliat - Norhalisah, Siti; Zubaidillah, Muh. Haris; Khafifah, Siti (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Vocabulary or mufradāt is one of the elements of language that needs to be mastered by foreign language learners, including Arabic. So it is necessary to master vocabulary to understand Arabic language learning. In learning Arabic, there must be problems in learning. Such as limited reading ability, lack of learning media, classroom conditions, and low vocabulary repetition. Therefore, this study aims to describe the mufradat learning process, identify the problems faced by students, and offer relevant solutions in mufradat learning at MTs An-Noor Paliat. The research uses a descriptive qualitative approach with data collection techniques in the form of interviews, observations, documentation, and literature studies. The results of the study showed that mufradat learning at MTs An-Noor Paliat found several problems including the ability to read Arabic writing, the lack of use of learning media, less conducive classroom conditions, and low repetition of mufradat at home. Some of the solutions that can be done include the use of learning media, improving classroom management, improving the ability to read Arabic writing, and getting used to repeating vocabulary at home. This study concludes that improving mufradat learning with appropriate and sustainable implementation and solutions is the key to improving students’ mastery of mufradat.